Mini Review on Active Sites in Ce-Based Electrocatalysts for Alkaline Water Splitting - Yu, Jun; Du, Xinjuan; Liu, Hongzhi; Qiu, Chen; Yu, Rongxing; Li, Simeng; Ren, Jiazheng; Yang, Shihe (Energy & fuels, 2021)
Hydrogen energy has become one of the most attractive candidates to replace traditional fossil fuels because of its lack of pollution and its high energy density. Electrocatalytic water splitting is a “green” and sustainable way to produce hydrogen but is still not sufficiently efficient at this stage. In recent years, Ce-based materials have become very popular as the electrocatalysts for water splitting primarily because of the multivalence state of Ce and easily formed oxygen vacancies readily formed in CeO2. However, until now, this interesting subject has seldom been reviewed, especially for electrocatalysts for alkaline water splitting. Herein, we outline and discuss recent progress on the active sites of Ce-based electrocatalysts for hydrogen evolution and oxygen evolution. Oxygen vacancies and interfaces between CeO2 and mixed metal components could provide optimized binding of hydrogen evolution reaction (HER) intermediates, thus promoting HER performance. For the oxygen evolution reaction (OER), Ce3+/Ce4+ redox, oxygen vacancies, and exogenous transition metals could optimize the binding of OER intermediates toward top catalytic activities. The aim of this review is to seek an overall understanding about the reaction sites in Ce-based electrocatalysts for water splitting, which may provide a guide for the future development of HER and OER Ce-based electrocatalysts toward industrial applications.